The family office : a practical guide to strategically and operationally managing family wealth /: a practical guide to strategically and operationally managing family wealth. (2018) - Canessa, Boris; Escher, Jens; Koeberle-Schmid, Alexander; Preller, Peter; (Banking relationship manager), Weber, Christoph
No abstract available